Creativity of Teachers in Creating Java Song in Industrial Era 4.0 - Rizqy, Titis (International Conference of Moslem Society, 2019)
Javanese literature includes a Javanese song which should remain popular among the millennial generation today which will meet the industrial era 4.0. The limitations of Javanese songs require teachers to increase innovation by means of continuous creativity to create Javanese songs where poetry and songs use compilation of existing songs. As well as the process of preserving Javanese songs, so that the growing age of Javanese, especially Javanese songs, is not left behind but still follows. Teacher creativity in the creation of Javanese song lyrics in the industrial revolution 4.0 era is based on song inspiration, the contents of song lyrics and the process of song lyrics.